High-performance palladium-carbon catalyst and preparation method thereof
By subjecting activated carbon to high-temperature calcination, acid washing, and modification, combined with specific solution treatment, the problem of uneven palladium dispersion in palladium-carbon catalysts was solved, achieving uniform distribution of palladium particles on activated carbon and high catalytic activity.
Patent Information
- Application Number
- CN202511613050.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-11-06
AI Technical Summary
Existing palladium-on-carbon catalysts suffer from uneven palladium dispersion and poor catalytic activity, mainly due to the limited porosity and specific surface area of activated carbon, which makes palladium crystals prone to agglomeration, affecting the activity and selectivity of the catalyst.
Activated carbon was treated with high-temperature calcination, acid washing and modification. Amino and thiol groups were introduced on the surface of the activated carbon by a mixed solution of amine compounds and sulfur-containing compounds as a modifier. Palladium salt solution was prepared by combining palladium chloride and hydrochloric acid solution, reduced by hydrazine hydrate solution, and finally activated in a hydrogen atmosphere to form uniformly distributed palladium nanoparticles.
This significantly improves the adsorption capacity and uniformity of palladium on activated carbon, avoids palladium particle agglomeration, enhances the catalytic activity and palladium dispersion of the catalyst, and forms a high-performance palladium-carbon catalyst.
Smart Images

Figure CN121060518A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of catalysts, and particularly relates to a high-performance palladium-carbon catalyst and a preparation method thereof. BACKGROUND
[0002] The palladium-carbon catalyst is a kind of catalytic material, which has the characteristics of small mass, high activity, stable performance, green environmental protection and easy recovery, and is applied in the medical industry, petrochemical industry, dye and perfume industry, electronic industry and other fine chemical reaction processes. The purified terephthalic acid is a basic raw material for the synthesis of polyethylene terephthalate, and a small amount of impurity p-carboxybenzaldehyde in the crude terephthalic acid will affect the esterification function of the purified terephthalic acid. In the industry, the palladium-carbon catalyst is usually used to convert the p-carboxybenzaldehyde into hydroxymethylbenzoic acid and p-methylbenzoic acid which are easily soluble in water under the action of the palladium-carbon catalyst, and then the separation and purification of the crude terephthalic acid are achieved through multiple crystallization, centrifugation and other operations. Therefore, the palladium-carbon catalyst plays a key role in the production process of the purified terephthalic acid.
[0003] In the catalytic reaction, the relationship between the balance selectivity, activity agent catalyst stability and one or more side reactions of the product often needs to be selected, so it is particularly important to select a suitable high-efficiency catalyst. The palladium-carbon catalyst belongs to a supported catalyst, and the commonly used preparation methods include impregnation method, hydrolysis impregnation method, ion exchange method and impregnation precipitation method. However, the current palladium-carbon catalyst still has many defects, such as the limited porosity and specific surface area of the activated carbon, which makes it difficult for the palladium active ingredient to be highly dispersed in the activated carbon, and the palladium grains are easy to agglomerate, thereby affecting the activity of the catalyst.
[0004] The Chinese patent application file with the publication number CN106732553A discloses a preparation method of a palladium-carbon catalyst, which includes the following steps: acid-base treatment is performed on the activated carbon to dissolve the impurities in the activated carbon and reduce the ash content in the activated carbon, the activated carbon is mixed with a hydrochloric acid solution with a mass fraction of 1%-5% at a mass ratio of 1:3-7, and then stirred uniformly, heated and boiled for 1-3 hours, filtered, washed with water twice, and dried in a 100℃ oven to obtain the activated carbon after acid treatment; the activated carbon after acid treatment is mixed with a sodium hydroxide solution with a mass fraction of 1%-5% at a mass ratio of 1:3-7, and then stirred uniformly. However, in the process of acidification treatment of the activated carbon, the initial ash content and pore structure of the activated carbon are not adjusted, and for the activated carbon with low ash content, boiling for 3 hours will cause the surface functional groups of the activated carbon to be excessively damaged, thereby affecting the adsorption and anchoring of the palladium in the subsequent process. In addition, the volatilization of the hydrochloric acid solution is accelerated during the boiling process, the effective concentration is reduced, the efficiency of the acid treatment is reduced, and after the acid treatment, the chloride ions will be left on the surface of the activated carbon. The residual chloride ions on the activated carbon will form stable complexes with the palladium ions, thereby affecting the reduction and dispersion of the palladium on the surface of the carrier, and reducing the catalytic performance of the palladium-carbon catalyst. SUMMARY
[0005] In order to solve the technical problems of uneven dispersion of palladium and poor catalytic activity in the prior art, the purpose of the present application is to provide a high-performance palladium carbon catalyst and a preparation method thereof.
[0006] In order to achieve the above purpose, the technical scheme of the present application is as follows: A preparation method of a high-performance palladium carbon catalyst, comprising the following steps: S1: granular coconut shell carbon is calcined under a nitrogen atmosphere for 2-4h, cooled, put into an acidic solution, stirred at 60-80℃ for 4-5h, washed, dried, and an acid-treated activated carbon is obtained; S2: the acid-treated activated carbon prepared in step S1 is mixed with a modifier, stirred under vacuum to 180-200℃, and reacted for 8-10h, then washed, dried, and a modified activated carbon is obtained; S3: the modified activated carbon prepared in step S2 is mixed with a palladium salt solution, ultrasonically treated for 4-5h under stirring, aged, then heated to 50-60℃, and a hydrazine hydrate solution is added dropwise under stirring, reacted for 2-4h, cooled, filtered, washed, and dried, and a palladium carbon catalyst crude product is obtained; S4: the palladium carbon catalyst crude product prepared in step S3 is heated to 300-400℃ under a hydrogen atmosphere, activated for 1.5-2h, cooled, and a high-performance palladium carbon catalyst is obtained; The modifier in step S2 is a mixed solution of amine-based compounds, sulfur-containing compounds and deionized water, the mass percentage of amine-based compounds is 4%-7%, and the mass percentage of sulfur-containing compounds is 10%-15%.
[0007] In the above scheme, the high-temperature calcination in step S1 can effectively remove volatile impurities and part of inorganic components on the surface of the activated carbon, expand the pore structure of the activated carbon, increase the specific surface area, and provide more space for the subsequent loading of palladium; the acid solution can further remove metal oxides and other impurities remaining on the surface of the activated carbon, improve the chemical properties of the surface of the activated carbon, introduce functional groups such as carboxyl and carbonyl groups to the surface of the activated carbon, and improve the adsorption capacity of the activated carbon for palladium ions. The modification of the acid-treated activated carbon with the mixed aqueous solution of the amine compound and the sulfur-containing compound in step S2 can introduce a large number of functional groups such as hydroxyl, carboxyl and carbonyl groups to the surface of the activated carbon, providing a basis for the subsequent loading of palladium; the ultrasonic treatment in step S3 can break the interfacial tension of the solution through the vibration and cavitation effect generated by the ultrasonic treatment, promote the penetration and adsorption of the palladium salt in the pores and on the surface of the activated carbon, effectively avoid the agglomeration of palladium, and use the hydrazine hydrate solution for reduction treatment to efficiently reduce the palladium ions adsorbed on the surface of the activated carbon into metallic palladium, and effectively control the production of palladium particles to form nano-palladium particles with uniform particle size and good dispersity; the high-temperature activation in a hydrogen atmosphere in step S4 can further remove a small amount of impurities and oxygen-containing functional groups remaining on the surface of the catalyst, enhance the interaction between the metallic palladium and the activated carbon, improve the stability of the palladium particles, and further improve the catalytic activity of the palladium-carbon catalyst.
[0008] Further, the temperature of the calcination in step S1 is 800-1000℃, and the heating rate is 5-8℃ / min.
[0009] Further, the mass percentage of the acid solution in step S1 is 50%-55%, and the acid solution is one of nitric acid solution, sulfuric acid solution and perchloric acid solution.
[0010] In the above scheme, the nitric acid solution, the sulfuric acid solution and the perchloric acid solution acidify and oxidize the coconut shell carbon to generate hydroxyl, carboxyl and carbonyl groups in situ on the surface, the carboxyl group can form stable bidentate chelation or ion pair with palladium ions, the carbonyl group can coordinate with palladium ions through lone pair electrons, and the oxygen-containing groups such as carboxyl and carbonyl groups can improve the pore wetting property of the coconut shell carbon, ensure the rapid entry of palladium ions into the micropore-mesopore interior, and improve the adsorption uniformity of palladium.
[0011] Further, the mass ratio of the granular coconut shell carbon to the acid solution in step S1 is 1:3-5.
[0012] Further, the mixing mass ratio of the acid-treated activated carbon to the modifier in step S2 is 1:7-10.
[0013] Further, the amine compound in the modifier is one or more of ethylenediamine, 1,3-propanediamine, diethylenetriamine and triethylenetetramine.
[0014] In the above scheme, the amino group in the amine-based compound can undergo dehydration condensation reaction with the hydroxyl group on the surface of the activated carbon, so that the amine-based compound is grafted to the surface of the activated carbon, and an amino group is introduced on the surface of the activated carbon. The nitrogen atom in the amino group has strong electronegativity and lone pair electrons, and can form a stable coordination bond with palladium ions, significantly improving the loading capacity and stability of the activated carbon for palladium, and further improving the catalytic activity of the palladium-carbon catalyst.
[0015] Further, the sulfur-containing compound in the modifier is one or more of thiourea, (2-hydroxyethyl) thiourea and 1,3-diethyl thiourea.
[0016] In the above scheme, the thiourea group in the sulfur-containing compound can form a hydrogen bond with the carboxyl group on the surface of the activated carbon. When heated under vacuum, thiourea will decompose, and the C=S bond in the molecule will break, forming a mercapto group (-SH) on the surface of the activated carbon. The combination of the sulfur atom in the mercapto group with the palladium ion belongs to the strong coordination of soft acid-soft base, and the binding force is extremely strong. The uniform distribution of mercapto groups on the surface of the activated carbon can effectively prevent the agglomeration of palladium particles, improve the dispersion of palladium, and further improve the palladium loading capacity and catalytic activity of the palladium-carbon catalyst.
[0017] Further, the preparation method of the palladium salt solution in step S3 is as follows: mixing palladium chloride with a mass percentage of 10%-15% hydrochloric acid aqueous solution, controlling the concentration of palladium chloride to be 0.05-0.1 mol / L, stirring for 0.5-1 h, adding citric acid, the mass of citric acid is 0.2%-0.5% of the mass of palladium chloride, continuing to stir for 10-20 min, and obtaining a palladium salt solution.
[0018] In the above scheme, palladium chloride and hydrochloric acid solution are used as the main components of the palladium salt solution. The palladium ions in the solution exist in the form of [PdCl] 2- complex ions, which can uniformly combine with active sites such as mercapto groups and amino groups on the surface of activated carbon, avoid agglomeration of palladium particles during loading, and [PdCl] 2- complex ions are easily reduced to Pd 0 during the subsequent reduction step, palladium particles grow slowly and have high dispersion, which is beneficial to improve the catalytic activity of the palladium-carbon catalyst. The presence of a small amount of citric acid can effectively prevent the premature precipitation of palladium ions during the loading process, form large-diameter palladium particles, and further improve the adsorption uniformity of palladium.
[0019] Further, the solid-liquid ratio of the modified activated carbon and the palladium salt solution in step S3 is 1:10-14, and the mass percentage of the hydrazine hydrate solution is 8%-12%. The molar ratio of hydrazine hydrate to palladium ions in the palladium salt solution is 2-2.5:1.
[0020] The application also provides a high-performance palladium-carbon catalyst prepared by the preparation method of the high-performance palladium-carbon catalyst.
[0021] Through the above scheme, the high-performance palladium carbon catalyst with uniformly dispersed palladium and good catalytic activity is prepared.
[0022] Compared with the prior art, the high-performance palladium carbon catalyst and the preparation method thereof have the following technical advantages: (1) The impurities on the surface of the activated carbon are effectively removed by high-temperature calcination, acid pickling and modification treatment, etc., the specific surface area and pore structure of the carrier are enlarged, a large number of functional groups are introduced, and the adsorption capacity and uniformity of the activated carbon carrier to palladium ions are significantly improved; (2) The activated carbon is modified by using an amine compound, a sulfur compound and a mixed solution of deionized water as a modifier, amino groups and mercapto groups are introduced on the surface of the activated carbon, palladium ions are adsorbed through chemical bonds, the adsorption capacity of the activated carbon to palladium is effectively improved, and the catalytic activity of the palladium carbon catalyst is improved; (3) The palladium chloride and hydrochloric acid solution are used as the main components of the palladium salt solution, and a small amount of citric acid is added to the palladium salt solution, so that the palladium ions are prevented from precipitating in advance during the loading process to form large-size palladium particles, which is beneficial to improving the dispersion of palladium and the catalytic activity of the palladium carbon catalyst. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 The transmission electron microscope image of the high-performance palladium carbon catalyst prepared in Example 3. DETAILED DESCRIPTION
[0024] The following will be further described in combination with specific examples, but the present application is not limited to the following examples. Those skilled in the art can make various modifications according to the basic idea of the present application, as long as they do not deviate from the basic idea of the present application, and they are within the scope of the present application.
[0025] Example 1 A preparation method of a high-performance palladium carbon catalyst, comprising the following steps: S1: Place the granular coconut shell carbon with a particle size of 100 mesh in a muffle furnace, and heat to 800℃ at a heating rate of 5℃ / min under a nitrogen atmosphere for 4h, cool to room temperature, and then put into a 50% nitric acid solution (the mass ratio of coconut shell carbon to acid solution is 1:3), stir at 60℃ for 4h, wash with deionized water until the washing liquid is neutral, and then put into a vacuum drying oven and dry at 80℃ for 12h to obtain acid-treated activated carbon; S2: The acid-treated activated carbon prepared in step S1 was mixed with a modifier (mass ratio of acid-treated activated carbon to modifier was 1:7), vacuumized to a vacuum degree of -0.02 MPa, stirred and heated to 180℃ at a rate of 5℃ / min, and kept at 180℃ for 8 h. After cooling to room temperature, the product was washed with deionized water until no sulfur ions were detected in the washing liquid (determined by using lead acetate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 100℃ for 15 h to obtain modified activated carbon; The modifier was a mixed solution of 1,3-propanediamine, thiourea and deionized water, the mass percentage of 1,3-propanediamine was 4%, and the mass percentage of thiourea was 10%; S3: The modified activated carbon prepared in step S2 was mixed with a palladium salt solution, and ultrasonic treatment was performed at a power of 200 W and a temperature of 30℃ for 4 h. After standing for 12 h, the product was heated to 50℃, and a 8% hydrazine hydrate solution was slowly added dropwise under stirring. The stirring was continued for 2 h, and then the product was cooled to room temperature, filtered, washed with deionized water until no chloride ions were detected in the washing liquid (determined by using silver nitrate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 70℃ for 15 h to obtain a crude palladium-carbon catalyst; The palladium salt solution was prepared by mixing palladium chloride with a 10% hydrochloric acid aqueous solution, controlling the concentration of palladium chloride to be 0.05 mol / L, stirring for 0.5 h, adding citric acid (the mass of citric acid was 0.2% of the mass of palladium chloride), and continuing to stir for 10 min; The solid-liquid ratio of modified activated carbon to palladium salt solution was 1:10, and the molar ratio of hydrazine hydrate to palladium ions in the palladium salt solution was 2:1; S4: The crude palladium-carbon catalyst prepared in step S3 was placed in a tube furnace, heated to 300℃ at a rate of 3℃ / min under a hydrogen atmosphere, and kept at 300℃ for 1.5 h. After cooling to room temperature, a high-performance palladium-carbon catalyst was obtained.
[0026] Example 2 A method for preparing a high-performance palladium-carbon catalyst, comprising the following steps: S1: Granular coconut shell carbon with a particle size of 120 mesh was placed in a muffle furnace, heated to 1000℃ at a rate of 8℃ / min under a nitrogen atmosphere, and kept at 1000℃ for 2 h. After cooling to room temperature, the product was placed in a 55% sulfuric acid solution (mass ratio of coconut shell carbon to acid solution was 1:5), stirred at 80℃ for 5 h, washed with deionized water until the washing liquid was neutral, and then dried in a vacuum drying oven at 100℃ for 8 h to obtain acid-treated activated carbon; S2: The acid-treated activated carbon prepared in step S1 was mixed with a modifier (mass ratio of acid-treated activated carbon to modifier was 1:10), vacuumized to a vacuum degree of -0.05 MPa, stirred and heated to 200℃ at a rate of 8℃ / min, and kept at 200℃ for 10 h. After cooling to room temperature, the product was washed with deionized water until no sulfur ions were detected in the washing liquid (determined by using lead acetate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 110℃ for 15 h to obtain modified activated carbon; The modifier was a mixed solution of diethylene triamine, (2-hydroxyethyl) thiourea and deionized water, the mass percentage of diethylene triamine was 7%, and the mass percentage of (2-hydroxyethyl) thiourea was 15%; S3: The modified activated carbon prepared in step S2 was mixed with a palladium salt solution, and ultrasonic treatment was performed at a power of 300 W and a temperature of 40℃ for 5 h. After standing for 16 h, the product was heated to 60℃, and a 12% hydrazine hydrate solution was slowly added dropwise under stirring. The stirring was continued for 4 h, and then the product was cooled to room temperature, filtered, washed with deionized water until no chloride ions were detected in the washing liquid (determined by using silver nitrate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 90℃ for 15 h to obtain a crude palladium-carbon catalyst; The palladium salt solution was prepared by mixing palladium chloride with a 15% hydrochloric acid aqueous solution, controlling the concentration of palladium chloride to be 0.1 mol / L, stirring for 1 h, adding citric acid (the mass of citric acid was 0.5% of the mass of palladium chloride), and continuing to stir for 20 min; The solid-liquid ratio of modified activated carbon to palladium salt solution was 1:14, and the molar ratio of hydrazine hydrate to palladium ions in the palladium salt solution was 2.5:1; S4: The crude palladium-carbon catalyst prepared in step S3 was placed in a tube furnace, heated to 400℃ at a rate of 5℃ / min under a hydrogen atmosphere, and kept at 400℃ for 2 h. After cooling to room temperature, a high-performance palladium-carbon catalyst was obtained.
[0027] Example 3 A method for preparing a high-performance palladium-carbon catalyst, comprising the following steps: S1: Granular coconut shell carbon with a particle size of 110 mesh was placed in a muffle furnace, heated to 950℃ at a rate of 7℃ / min under a nitrogen atmosphere, and kept at 950℃ for 3.2 h. After cooling to room temperature, the product was placed in a 53% perchloric acid solution (mass ratio of coconut shell carbon to acid solution was 1:4), stirred at 70℃ for 4.5 h, washed with deionized water until the washing liquid was neutral, and then dried in a vacuum drying oven at 90℃ for 11 h to obtain acid-treated activated carbon; S2: The acid-treated activated carbon prepared in step S1 was mixed with a modifier (mass ratio of acid-treated activated carbon to modifier was 1:9), vacuumized to a vacuum degree of -0.04 MPa, stirred and heated to 190℃ at a rate of 6℃ / min, and kept at 190℃ for 9 h. After cooling to room temperature, the product was washed with deionized water until no sulfur ions were detected in the washing liquid (determined by using lead acetate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 105℃ for 13 h to obtain modified activated carbon; The modifier was a mixed solution of amine-based compound, sulfur-containing compound and deionized water, the mass percentage of the amine-based compound was 5%, and the mass percentage of the sulfur-containing compound was 13%. The amine-based compound was composed of ethylenediamine and triethylenetetramine at a mass ratio of 1:3, and the sulfur-containing compound was composed of (2-hydroxyethyl) thiourea and 1,3-diethyl thiourea at a mass ratio of 1:1. S3: The modified activated carbon prepared in step S2 was mixed with a palladium salt solution, and ultrasonic treatment was performed at a power of 250 W and a temperature of 35℃ for 4.5 h. After standing for 14 h, the product was heated to 55℃, and a 10% hydrazine hydrate solution was slowly added dropwise under stirring. The stirring was continued for 3 h, and then the product was cooled to room temperature, filtered, washed with deionized water until no chloride ions were detected in the washing liquid (determined by using silver nitrate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 80℃ for 13 h to obtain a crude palladium-carbon catalyst. The palladium salt solution was prepared by mixing palladium chloride with a 13% hydrochloric acid aqueous solution, controlling the concentration of the palladium chloride to be 0.08 mol / L, stirring for 0.8 h, adding citric acid (the mass of the citric acid was 0.4% of the mass of the palladium chloride), and continuing to stir for 15 min. The solid-liquid ratio of the modified activated carbon to the palladium salt solution was 1:12, and the molar ratio of hydrazine hydrate to palladium ions in the palladium salt solution was 2.2:1. S4: The crude palladium-carbon catalyst prepared in step S3 was placed in a tube furnace, heated to 350℃ at a rate of 4℃ / min under a hydrogen atmosphere, and kept at 350℃ for 1.8 h. After cooling to room temperature, a high-performance palladium-carbon catalyst was obtained.
[0028] Example 4 A method for preparing a high-performance palladium-carbon catalyst, comprising the following steps: S1: Granular coconut shell carbon with a particle size of 110 mesh was placed in a muffle furnace, heated to 950℃ at a rate of 7℃ / min under a nitrogen atmosphere, and kept at 950℃ for 3.2 h. After cooling to room temperature, the product was placed in a 53% perchloric acid solution (mass ratio of coconut shell carbon to acid solution was 1:4), stirred at 70℃ for 4.5 h, washed with deionized water until the washing liquid was neutral, and then dried in a vacuum drying oven at 90℃ for 11 h to obtain acid-treated activated carbon. S2: The acid-treated activated carbon prepared in step S1 was mixed with a modifier (the mass ratio of the acid-treated activated carbon to the modifier was 1:8), vacuumized to a vacuum degree of -0.04 MPa, stirred and heated to 195℃ at a rate of 6℃ / min, and kept at the temperature for 9.2 h. After cooling to room temperature, the product was washed with deionized water until no sulfur ions were detected in the washing liquid (determined by using lead acetate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 105℃ for 13 h to obtain modified activated carbon; The modifier was a mixed solution of triethylenetetramine, 1,3-diethylthiourea and deionized water, the mass percentage of triethylenetetramine was 5%, and the mass percentage of 1,3-diethylthiourea was 13%. S3: The modified activated carbon prepared in step S2 was mixed with a palladium salt solution, and ultrasonic treatment was performed at a power of 250 W and a temperature of 35℃ for 4.5 h. After standing for 14 h, the product was heated to 55℃, and a 10% hydrazine hydrate solution was slowly added dropwise under stirring. The stirring was continued for 3 h, and then the product was cooled to room temperature, filtered, washed with deionized water until no chloride ions were detected in the washing liquid (determined by using silver nitrate solution, and no white precipitate was generated), and then dried in a vacuum drying oven at 80℃ for 13 h to obtain a crude palladium-carbon catalyst. The palladium salt solution was prepared by mixing palladium chloride with a 12% hydrochloric acid aqueous solution, controlling the concentration of the palladium chloride to be 0.07 mol / L, stirring for 0.8 h, adding citric acid (the mass of the citric acid was 0.3% of the mass of the palladium chloride), and continuing to stir for 15 min. The solid-liquid ratio of the modified activated carbon to the palladium salt solution was 1:12, the mass percentage of the hydrazine hydrate solution was 10%, and the molar ratio of the hydrazine hydrate to palladium ions in the palladium salt solution was 2.2:1. S4: The crude palladium-carbon catalyst prepared in step S3 was placed in a tube furnace, heated to 350℃ at a rate of 4℃ / min under a hydrogen atmosphere, and kept at the temperature for 1.8 h. After cooling to room temperature, a high-performance palladium-carbon catalyst was obtained.
[0029] Comparative Example 1 In the comparative example, the palladium-carbon catalyst was prepared by a method similar to that of Example 3, and the difference between the comparative example and Example 3 was that an equal amount of an amine-based compound was used instead of a sulfur-containing compound in step S2 of the comparative example, and the types of the amine-based compounds were the same as those of Example 3.
[0030] Comparative Example 2 In the comparative example, the palladium-carbon catalyst was prepared by a method similar to that of Example 3, and the difference between the comparative example and Example 3 was that an equal amount of a sulfur-containing compound was used instead of an amine-based compound in step S2 of the comparative example.
[0031] Comparative Example 3 The preparation method of the palladium-carbon catalyst in the present comparative example is similar to that in Example 3, and the difference between the present comparative example and Example 3 is that the amine compound in the modifier in step S2 of the present comparative example is ethanolamine.
[0032] Comparative Example 4 The preparation method of the palladium-carbon catalyst in the present comparative example is similar to that in Example 3, and the difference between the present comparative example and Example 3 is that the preparation method of the palladium salt solution in step S3 of the present comparative example uses an equal amount of deionized water instead of citric acid.
[0033] Comparative Example 5 The preparation method of the palladium-carbon catalyst in the present comparative example is similar to that in Example 3, and the difference between the present comparative example and Example 3 is that the acid solution in step S1 of the present comparative example is a hydrochloric acid solution.
[0034] Test Example Palladium content test: 0.5007 g of palladium-carbon catalyst was weighed, and under heating conditions, aqua regia + hydrofluoric acid was added to the palladium-carbon catalyst in multiple times until it was completely dissolved. After being diluted to 500 mL, it was shaken well, 10 mL was taken with a colorimetric tube, 2 mL of 4.5 mol / L sulfuric acid, 2.5 mL of potassium iodide solution, 2 mL of ascorbic acid solution were added in turn, and finally diluted to 25 mL, shaken well and placed in the dark for 10 minutes. The absorbance was measured at a wavelength of 316 nm with a 1 cm cuvette by a spectrophotometer, and the standard curve was brought in to calculate the palladium content (w Pd ).
[0035] Palladium dispersion test: CO chemisorption method was used to determine the dispersion of palladium in the catalyst. The specific method is as follows: the catalyst was reduced under hydrogen atmosphere at 300°C for 1 h, cooled to room temperature, and then CO gas was introduced for adsorption. The dispersion of palladium (D) was calculated by measuring the adsorption amount of CO, D = (V CO × M Pd ) / (w Pd × 10 6 ) × 100%, wherein V CO is the adsorption amount of CO measured by a chemisorption instrument, M Pd is the molar mass of palladium, and w Pd is the palladium content in the palladium-carbon catalyst.
[0036] Catalytic activity test: The reaction of nitrobenzene hydrogenation to prepare aniline was used as a model reaction to test the catalytic activity of the catalyst. The reaction conditions were as follows: nitrobenzene 0.1 mol, ethanol 50 mL, catalyst dosage 1% of the mass of nitrobenzene, hydrogen pressure 1.0 MPa, reaction temperature 80°C, reaction time 2 h. After the reaction was completed, the reaction products were analyzed by high performance liquid chromatography (HPLC), and the conversion rate of nitrobenzene and the selectivity of aniline were calculated to evaluate the catalytic activity of the catalyst.
[0037] The test results are shown in Table 1.
[0038] Table 1 Performance Test Results
[0039] As shown in Table 1, the high-performance palladium-on-carbon catalyst provided by the present invention has a palladium content of 2.8%-3.2%, a palladium dispersion of 88.9%-91.2%, a p-nitrobenzene conversion rate of 96.5%-98.9%, and a aniline selectivity of 97.9%-99.2%. This indicates that the high-performance palladium-on-carbon catalyst prepared by the present invention has a high palladium content and a high palladium dispersion on the activated carbon support, resulting in good catalytic activity.
[0040] In addition, the high-performance palladium-on-carbon catalyst prepared in Example 3 was subjected to transmission electron microscopy (TEM) testing, and the test results are shown in [Figure 1]. Figure 1 .Depend on Figure 1 It can be seen that the palladium particles in the high-performance palladium-carbon catalyst provided by the present invention do not exhibit obvious agglomeration and are uniformly distributed at the micropores and mesopore inlets of the activated carbon.
[0041] The above embodiments are merely illustrative of the present invention and are not intended to limit the invention. Those skilled in the art should not modify the above embodiments without departing from the spirit and scope of the present invention. All equivalent modifications or alterations made by those skilled in the art without departing from the technical concept of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a high performance palladium on carbon catalyst, characterized in that, The method comprises the following steps: S1: roasting the granular coconut shell carbon in a nitrogen atmosphere for 2-4 hours, cooling, putting into an acid solution, stirring at 60-80℃ for 4-5 hours, washing, drying, and obtaining the acid-treated activated carbon; S2: mixing the acid-treated activated carbon obtained in step S1 with a modifier, stirring under vacuum, heating to 180-200℃, and keeping the temperature for 8-10 hours, then washing, drying, and obtaining the modified activated carbon; S3: mixing the modified activated carbon obtained in step S2 with a palladium salt solution, ultrasonic treatment for 4-5 hours under stirring, standing, then heating to 50-60℃, and adding hydrazine hydrate solution dropwise under stirring, reacting for 2-4 hours, cooling, filtering, washing, and drying to obtain the crude palladium-carbon catalyst; S4: heating the crude palladium-carbon catalyst obtained in step S3 to 300-400℃ under hydrogen atmosphere, activating for 1.5-2 hours, and cooling to obtain the high-performance palladium-carbon catalyst. The modifier in step S2 is a mixed solution of amine-based compounds, sulfur-containing compounds, and deionized water, the mass percentage of the amine-based compounds is 4%-7%, and the mass percentage of the sulfur-containing compounds is 10%-15%.
2. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The roasting temperature in step S1 is 800-1000℃, and the heating rate is 5-8℃ / min.
3. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The mass percentage of the acid solution in step S1 is 50%-55%, and the acid solution is one of nitric acid solution, sulfuric acid solution, and perchloric acid solution.
4. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The mass ratio of the granular coconut shell carbon to the acid solution in step S1 is 1:3-5.
5. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The mixing mass ratio of the acid-treated activated carbon to the modifier in step S2 is 1:7-10.
6. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The amine-based compounds in the modifier are one or more of ethylenediamine, 1,3-propanediamine, diethylenetriamine, and triethylenetetramine.
7. The method of making a high performance palladium on carbon catalyst according to claim 1, wherein, The sulfur-containing compounds in the modifier are one or more of thiourea, (2-hydroxyethyl) thiourea, and 1,3-diethylthiourea.
8. The method of making a high performance palladium on carbon catalyst of claim 1, wherein, The preparation method of the palladium salt solution in step S3 is as follows: mixing palladium chloride with 10%-15% hydrochloric acid aqueous solution, controlling the concentration of palladium chloride to be 0.05-0.1 mol / L, stirring for 0.5-1 hour, adding citric acid, the mass of citric acid being 0.2%-0.5% of the mass of palladium chloride, continuing to stir for 10-20 minutes, and obtaining the palladium salt solution.
9. The method of making a high performance palladium on carbon catalyst of claim 1, wherein, The solid-liquid ratio of the modified activated carbon to the palladium salt solution in step S3 is 1:10-14, the mass percentage of the hydrazine hydrate solution is 8%-12%, and the molar ratio of hydrazine hydrate to palladium ions in the palladium salt solution is 2-2.5:
1.
10. The high-performance palladium-carbon catalyst prepared by the method according to any one of claims 1-9.
Citation Information
Patent Citations
Preparation method of palladium-charcoal catalyst
CN106732553A
Catalyst for direct methanoic acid fuel cell and method for producing the same
CN101269325A
A novel method for preparing supported composite metal catalysts and its application
CN102266784A
Preparation method of size-controllable nano Pd / C catalyst
CN103769088A
Nitrogenous ligand hemicelluloses-palladium catalyst as well as preparation method and application thereof
CN105013532A
Cited By
Adsorption method for directionally trapping palladium by activated carbon in strong-acidity high-chlorine medium
CN121847110A
A method for adsorbing palladium in a strong acidic high-chlorine medium by activated carbon
CN121847110B